Scleral Buckling for Retinopathy of Prematurity: A Case Report - Permanik, Gustiandari Fidhya; Barliana, Julie Dewi; Yudantha, Anggun Rama (Majalah Oftalmologi Indonesia, 2025)
IntroductionThe selection of management for advanced retinopathy of prematurity (ROP) requires careful consideration. The purpose of this study is to report the effectiveness of scleral buckling in patient with retinopathy of prematurity stage 4B of both eyes within 3 months. Case Description A 4-month-old female baby came to the Pediatric Ophthalmology Unit in Cipto Mangunkusumo General Hospital (RSCM) Kirana with chief complain did not make eye contact of both eyes. Her eyes were moving on their own since she was 3.5 months old, and sometimes squint. The patient came to the pediatrician and was referred to pediatric ophthalmology for further treatment. There was a history of premature delivery at 30 weeks with oxygen therapy for 3 weeks. The Pediatric ophthalmology division performed ultrasonography and retcam, and the diagnosis of retinopathy of prematurity stage 4B of both eyes was made. Scleral buckling was performed in the right and left eyes at the postmenstrual age of 49 weeks, and 52 weeks respectively by vitreoretinal division. Conclusion The management of ROP depends on the type ROP. For advanced ROP, surgery is indicated. The scleral buckle is a treatment option for advanced retinopathy of prematurity patients with retinal detachment if it is assumed that intraocular surgery presents a greater risk. In short-term period, for the right eye, the scleral buckling is effective. Further time to follow up is needed to show the long-term period effectiveness of scleral buckling in patients with advanced ROP.